Assessment of Depression and Its Associated Factors among Dental Outpatients - Shazia Sarwat Iqbal; Syed Muhammad Zulfiqar Hyder Naqvi; Syed Imtiaz Ahmed Jafry; Muhammad Zafar Iqbal Hydrie; Mudassir Hussain; Tariq Ali Adnan (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Abstract Objective: To assess depression and its associated factors among patients coming to the dental OPD of a public and a private dental college of Karachi. Methods: A cross-sectional study was carried out in public and a private dental college of Karachi from November 2018 to May 2019. The inclusion criterion of the study was being 18 years of age or above whereas those who refused to give written informed consent were excluded from the study. After checking eligibility and taking written informed consent, a total of 250 participants were included in the study using systematic random sampling. These dental outpatients were interviewed by the principal investigator with the help of a pretested structured questionnaire that contained questions about socio-demographic information, dental risk factors and questions from Patient Health Questionnaire-9. Data were analyzed on the statistical package for social sciences version 21. Inferential analysis was performed using chi-square test whereas the significance level was set at 0.05. Results: The study results revealed that 70 (28.0%) participants had minimal depression, 99 (39.6%) had mild depression, 45 (18.0%) had moderate depression, 28 (11.2%) had moderately severe depression whereas 8 (3.2%) had severe depression. Moreover, among demographic characteristics, only monthly income (p=0.037) and family history of depression (p<0.001) were found to be significantly associated with severity of depression whereas, regarding dental risk factors only frequent dental pain (p=0.014), increased sensitivity (p=0.001) and presence of any systemic morbidity (p=0.001) were found to be significantly associated with severity of depression. Conclusion: The study results revealed that almost a third of the dental outpatients had moderate, moderately severe or severe depression. Moreover, low monthly income, positively family history of depression, frequent dental pain, increased sensitivity and presence of any systemic morbidity were identified as factors associated with depression among the study participants